Observações preliminares sobre a periodicidade e taxa de crescimento em árvores tropicais - Vetter, Roland E.; Botosso, Paulo César (Acta Amazonica, 1988)
Preliminary results of periodicity and increment rate of Cardeiro (Scleronema micranthum Ducke, Bombacaceae) are presented. A cyclic periodicity has been observed. The increment data are strongly correlated to those reported from French Guyana.